2007
DOI: 10.1176/ajp.2007.164.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Training for Supported Employment: 2-3 Year Outcomes of a Randomized Controlled Trial

Abstract: The findings support the feasibility of integrating cognitive rehabilitation into supported employment programs and suggest that more research is warranted to evaluate the effects of the Thinking Skills for Work Program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 229 publications
(115 citation statements)
references
References 32 publications
3
108
2
1
Order By: Relevance
“…Several randomized controlled trials have suggested promising effects of combining cognitive remediation with supported employment (McGurk, Mueser, Feldman, Wolfe, & Pascaris, 2007;McGurk, Mueser, & Pascaris, 2005) and other models of vocational rehabilitation (Bell, Bryson, Greig, Corcoran, & Wexler, 2001;Bell, Bryson, Greig, Fiszdon, & Wexler, 2005;Lindenmayer et al, 2008;Vauth et al, 2005). These studies have been conducted in a variety of settings, such as at community mental health or rehabilitation centers, or in hospitals, but in all cases the locus of the intervention has been a mental health treatment center.…”
Section: )mentioning
confidence: 99%
“…Several randomized controlled trials have suggested promising effects of combining cognitive remediation with supported employment (McGurk, Mueser, Feldman, Wolfe, & Pascaris, 2007;McGurk, Mueser, & Pascaris, 2005) and other models of vocational rehabilitation (Bell, Bryson, Greig, Corcoran, & Wexler, 2001;Bell, Bryson, Greig, Fiszdon, & Wexler, 2005;Lindenmayer et al, 2008;Vauth et al, 2005). These studies have been conducted in a variety of settings, such as at community mental health or rehabilitation centers, or in hospitals, but in all cases the locus of the intervention has been a mental health treatment center.…”
Section: )mentioning
confidence: 99%
“…As summarized in Table 1, the cognitive programs were multi-faceted, and differed in intensity, duration, and types of computerized task practice, as well as use of strategy coaching and compensatory strategies. Furthermore, the level of difficulty of cognitive remediation exercises in two studies was based on clients' performance on the exercises, while other programs (Vauth et al, 2005;McGurk et al, 2005McGurk et al, , 2007 provided a standard curriculum. In addition, there were dif- (Bracy, 1995) over 26 weeks, combined with weekly social and work processing groups.…”
Section: Combination Of Cognitive Remediation and Vocational Rehabilimentioning
confidence: 99%
“…Previous nonrandomized studies have demonstrated promising results in including cognitive rehabilitation in traditional vocational rehabilitation for civilians with TBI [22,[43][44]. In a recent study focused on OIF/OEF Veterans with mTBI to moderate TBI, incorporation of cognitive rehabilitation services and SE was found to be beneficial in reducing mental health symptoms, improving self-report of postconcussive symptoms, and boosting attainment of competitive employment [45].…”
Section: Summary Of Quantitative Findings and Implicationsmentioning
confidence: 99%
“…Unfortunately, despite the many benefits of employment, Veterans and civilians who experience mTBI and/ or have MI often have significant difficulty getting their vocational needs met [10,[21][22][23][24]. Work plays a significant role in how people identify themselves and how they are described by their families, communities, and society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation